Variations in cancer care for adolescents and young adults (AYAs) with ductal carcinoma in situ. Issue 4 (2nd March 2018) - Voci, Amy; Bandera, Bradley; Ho, Emily; Lee, Jihey; Goldfarb, Melanie; DiNome, Maggie
Abstract: NCCN guidelines recommend tamoxifen (TAM) for adjuvant treatment of ductal carcinoma in situ (DCIS). TAM has side effects that can potentially complicate treatment recommendations and patient acceptance. It is unknown how well‐accepted this recommended therapy is for the adolescent and young adult (AYA) patient population with DCIS. The NCDB was used to identify patients aged 15‐39 with DCIS treated between 2000 and 2012. Patient demographic, socioeconomic, and treatment data were collected. Chi‐squared test and multivariate analysis were used for statistical assessment. A total of 3988 women were identified of which 1795 (45%) were recommended for endocrine therapy. Age > 30 (OR 1.31, 95%CI 1.01‐1.70), Black (OR 1.40, 95% CI 1.12‐1.65), or Asian (OR 1.45, 95% CI 1.08‐1.94) race, treatment at a nonacademic facility (OR 0.71, 95% CI 0.56‐0.91), geographic location of treating facility, receipt of radiation (OR 5.30, 95% CI 4.59‐6.11), and negative margins (OR 2.14, 95% CI 1.47‐3.11) were significant predictors of recommendation for endocrine therapy. Of those recommended, 1484 (83%) accepted treatment. Age, race, and annual income were significant variables affecting acceptance. Overall, only 37.2% (1484 of 3988) of women in this study initiated endocrine therapy for treatment of DCIS. Our results demonstrate that little over a third of patients in the AYA cohort receive endocrine therapy as treatment for DCIS. The bias appears to lie in physician recommendation because when recommended, the majority of patients accept treatment. Factors exist both medical and nonmedical that appear to influence these treatment decisions.